Irrigation investment in Myanmar: Potential for expansion - Rosegrant, Mark W.; Xie, Hua; Valmonte-Santos, Rowena; Michigan State University (International Food Policy Research Institute, 2019)
Myanmar is home to 54 million people, of whom 70 percent live in rural areas (MOALI 2016). In 2014, agriculture contributed 30 percent of gross domestic product (GDP), 16 percent of total export earnings, and 50 percent of total employment (MOALI 2016). Given the key role of agriculture in the national economy, agricultural development has been high on Myanmar’s national development agenda and irrigation is a key component of it. Irrigation can address freshwater shortages, especially during the dry season, and reduce the impacts of rainfall variability in the monsoon season. Irrigation has the potential to both increase rice production and expand the production of other crops, such as pulses, oil crops, and vegetables. Of the 12 million hectares (ha) with crops in 2014, about 7 million ha were devoted to rice. Currently, irrigation supplies about 2.2 million ha, or 18 percent, of the country’s total harvested area. The advantages of applying irrigation include increases in crop yield, protection of crops from inadequate rainfall and drought, enabling dry season cropping, creating the potential for crop diversification into higher‐valued crops, and crop area expansion to promote farm technologies and higher efficiencies (adaptation options in the face of climate change). Furthermore, effective development of affordable irrigation and water resources can improve agricultural production and enhance income and food security. This Project Policy Note summarizes key findings from the analysis of the development potential of irrigated agriculture in Myanmar.